'Farmer-born peasant-bred': agriculture, modernity and socio-ecological vision in Niyi Osundare's Village Voices and The Eye of the Earth. Issue 4 (1st October 2020) - Egya, Sule Emmanuel
ABSTRACT: Niyi Osundare is one of Nigeria's most celebrated poets. Scholars working on his poetry are unanimous on what they see as his use of nature imagery, largely hinged on pastoral agriculture. He sings brilliantly of his father's farms, of his childhood memories, and of the changing society in the face of modernity. A tension between African tradition and modernity is felt throughout his poetry. In this reading of Village Voices and The Eye of the Earth, situated within the postcolonial ecocritical problematic, I examine his portrayal of pre-modern pastoralism, the suspicion conveyed by his severe reflection on modernity, and his socio-ecological vision. I make the point that Osundare's poetry marks the juncture at which Anglophone Nigerian poetry derives its aesthetic framing from a valorisation of bucolic localities. I conclude that Osundare's poetry remains a site to expand the scope of postcolonial ecocriticism to embrace agrarian ecology.